2019
DOI: 10.2147/ppa.s204246
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparing quality of life and treatment satisfaction between patients on warfarin and direct oral anticoagulants: a cross-sectional study</p>

Abstract: Introduction and aim Patient quality of life (QOL) while on long-term oral anticoagulant therapy has been receiving greater attention in recent years due to the increase in life expectancy brought about by advances in medical care. This study aimed to compare the QOL, treatment satisfaction, hospitalization and bleeding rate in patients on long-term warfarin versus direct oral anticoagulants (DOAC). Methods This was a cross-sectional study of patients with non-valvular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
3
26
1
4
Order By: Relevance
“…On the other hand, Balci et al reported signi cant improvement in every domain of SF-12v2 (all p < 0.001), (38) while de Caterina et al reported signi cant improvement in severe mobility problem (p = 0.003), pain/discomfort (p = 0.035), and anxiety/depression (p < 0.001) of EuroQoL Instrument 5 levels (EQ-5D-5L) among NVAF patients after switching from warfarin to DOAC. (39) The patients in the current study had slightly higher value in each domain of the SF-12v2 except SF, but much lower mean TTR (47.0% versus 54.9%) and proportion with good TTR (24.3% versus 45.0%) when compared to similar subgroup of patients reported in Ng et al (34) Both studies were conducted in the anticoagulant clinic of a tertiary hospital, but the latter located in the Peninsular of Malaysia. The better social functioning among patients with good TTR in the current study could be due to their higher education level.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…On the other hand, Balci et al reported signi cant improvement in every domain of SF-12v2 (all p < 0.001), (38) while de Caterina et al reported signi cant improvement in severe mobility problem (p = 0.003), pain/discomfort (p = 0.035), and anxiety/depression (p < 0.001) of EuroQoL Instrument 5 levels (EQ-5D-5L) among NVAF patients after switching from warfarin to DOAC. (39) The patients in the current study had slightly higher value in each domain of the SF-12v2 except SF, but much lower mean TTR (47.0% versus 54.9%) and proportion with good TTR (24.3% versus 45.0%) when compared to similar subgroup of patients reported in Ng et al (34) Both studies were conducted in the anticoagulant clinic of a tertiary hospital, but the latter located in the Peninsular of Malaysia. The better social functioning among patients with good TTR in the current study could be due to their higher education level.…”
Section: Discussionsupporting
confidence: 45%
“…Most of the existing studies either compare the HRQoL of these patients versus those on DOAC, or in a longitudinal manner. Ng et al, (34) Benzimra et al, (35) Contreras et al, (36) and Alegret et al, (37) have reported no signi cant difference in the HRQoL of patients with NVAF receiving long-term warfarin versus DOAC in real-world scenario. On the other hand, Balci et al reported signi cant improvement in every domain of SF-12v2 (all p < 0.001), (38) while de Caterina et al reported signi cant improvement in severe mobility problem (p = 0.003), pain/discomfort (p = 0.035), and anxiety/depression (p < 0.001) of EuroQoL Instrument 5 levels (EQ-5D-5L) among NVAF patients after switching from warfarin to DOAC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Balci et al reported signi cant improvement in every domain of SF-12v2 (all p < 0.001),(34) while de Caterina et al reported signi cant improvement in severe mobility problem (p = 0.003), pain/discomfort (p = 0.035), and anxiety/depression (p < 0.001) of EuroQoL Instrument 5 levels (EQ-5D-5L) among NVAF patients after switching from warfarin to DOAC. (35) The patients in the current study had slightly higher value in each domain of the SF-12v2 except SF, but much lower mean TTR (47.0% versus 54.9%) and proportion with good TTR (24.3% versus 45.0%) when compared to similar subgroup of patients reported in Ng et al (30) Both studies were conducted in the anticoagulant clinic of a tertiary hospital, but the latter located in the Peninsular of Malaysia. The better social functioning among patients with good TTR in the current study could be due to their higher education level.…”
Section: Treatment Satisfactionsupporting
confidence: 45%
“…Most of the existing studies either compare the HRQoL of these patients versus those on DOAC, or in a longitudinal manner. Ng et al, (30) Benzimra et al, (31) Contreras et al, (32) and Alegret et al, (33) have reported no signi cant difference in the HRQoL of patients with NVAF receiving long-term warfarin versus DOAC in real-world scenario. On the other hand, Balci et al reported signi cant improvement in every domain of SF-12v2 (all p < 0.001),(34) while de Caterina et al reported signi cant improvement in severe mobility problem (p = 0.003), pain/discomfort (p = 0.035), and anxiety/depression (p < 0.001) of EuroQoL Instrument 5 levels (EQ-5D-5L) among NVAF patients after switching from warfarin to DOAC.…”
Section: Treatment Satisfactionmentioning
confidence: 99%
“…Oztürk et al reported that 33.3% of the patients had experienced minor and/or major bleeding at least once during 1year period, moreover bleeding complications detected in 38.9% of patients ≥ 65 years of age and in 26.2% of patients <65 years of age 25 . A recent study showed that the clinically relevant minor bleeds and severe bleeding events were found 66.7% in the warfarin treatment group during the two-year follow-up 26 . In the present study, minor bleeding rate was found 21.1%.…”
Section: Discussionmentioning
confidence: 97%